2014
DOI: 10.1007/s10637-014-0170-x
|View full text |Cite
|
Sign up to set email alerts
|

Phase I dose-escalation study evaluating safety, tolerability and pharmacokinetics of MEDI-573, a dual IGF-I/II neutralizing antibody, in Japanese patients with advanced solid tumours

Abstract: MEDI-573 is well tolerated at the doses investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 11 publications
0
22
0
1
Order By: Relevance
“…These findings are consistent with two phase 1 studies of dusigitumab, which reported SD in Caucasian (US) and Asian (Japanese) patients. 9,10 The results of the BLRM, integrating biomarkers (plateau in total IGF-1; inhibition of IGF bioactivity), and efficacy data from patients in both studies, provided further confirmation of the RBD. In the BLRM model, the estimated probability of having reached the RBD with a dose of 1000 mg was 87%, indicating that saturation of total IGF-1 biomarker, inhibition of IGF bioactivity, and disease control would plateau around this dose.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…These findings are consistent with two phase 1 studies of dusigitumab, which reported SD in Caucasian (US) and Asian (Japanese) patients. 9,10 The results of the BLRM, integrating biomarkers (plateau in total IGF-1; inhibition of IGF bioactivity), and efficacy data from patients in both studies, provided further confirmation of the RBD. In the BLRM model, the estimated probability of having reached the RBD with a dose of 1000 mg was 87%, indicating that saturation of total IGF-1 biomarker, inhibition of IGF bioactivity, and disease control would plateau around this dose.…”
Section: Discussionmentioning
confidence: 71%
“…1 The finding that drug-related hyperglycaemia was rare with xentuzumab (no patients in study 1280.1 and two patients in study 1280.2 [grade 1 and grade 3]) is consistent with clinical studies of another IGF-ligand blocking mAb, dusigitumab (MEDI-573). 9,10 The low incidence of hyperglycaemia with xentuzumab suggests that the anti-ligand mechanism of action may be more favourable than IGF-1R-targeted therapies with regard to hyperglycaemia. The immunogenic reaction to xentuzumab was low; however, no firm conclusions on ADA incidence and prevalence could be made in either study due to a high frequency of samples being deemed ADA inconclusive.…”
Section: Discussionmentioning
confidence: 99%
“…Currently two IGF ligand-capturing antibodies are evaluated in phase I clinical trials, MEDI-573 and BI 836845 respectively [94,95]. Phase I dose-escalation and safety studies show MEDI-573 to be well tolerated (NCT01340040) [96]. For BI 836845a phase I trial has been completed but no results have been published so far (NCT01403974).…”
Section: Targeting Igf-i and Igf-iimentioning
confidence: 99%
“…In a phase I trial MEDI-573 was well tolerated but failed to achieve partial or complete responses in HCC patients[51]. A study in Japanese patients with advanced solid tumors produced similar results[52]. EM164 is a humanized anti-IGF-1R antibody that inhibits signaling through IGF-1R.…”
Section: Signaling Disruptionmentioning
confidence: 99%